Mobilization of Da'wah Resources for Chinese Muslims in Indonesia - Pangestu, Perdana Putra (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2023)
The Indonesia Chinese Muslim Association (Persatuan Islam Tionghoa Indonesia /PITI) is an organization that has a unique role and phenomenon in Indonesia. The PITI phenomenon is related to the integration and role of the Chinese ethnic group in the realm of Islam in Indonesia. As a religious organization, PITI aims to integrate Chinese groups in Indonesia on an internal religious and ethnic basis. It is due to the long and complex history of the role of ethnic Chinese in Indonesian society, which includes various religious beliefs and beliefs. This article discusses the revitalization of the Da'wah of Chinese Muslims by PITI. PITI is considered an embryo that reinforces the existence of ethnic Chinese in the social arena, especially in establishing relations with natives. PITI should be able to maximize this role to convey opinions and ideas through cadres and utilize existing resources. The author uses a qualitative model by prioritizing the paradigm of social preaching. The analysis in this article will be presented through the results of elaboration with Oberschall's resource mobilization theory, aiming to determine the aspect of resources in the succession of social movements (da’wah). This article has the results of a study that PITI must be a pioneer in alleviating the social disparities that reverberate around natives, Muslims, and Chinese. The effort can be made to optimize their resources to share fresh narratives through their various da'wah channels.